Maternal neonicotinoid pesticide exposure impairs glucose metabolism by deteriorating brown fat thermogenesis - Wenwen Zhu; Jiali Fang; Chenbo Ji; Hong Zhong; Tianying Zhong; Xianwei Cui (Ecotoxicology and Environmental Safety)
Background: Neonicotinoids (NEOs) are well-designed highly selective pesticides that target nicotinic acetylcholine receptors. However, their extensive use, accumulation, and biomagnification pose significant risks to humans. Increasing evidence has suggested that NEOs may affect glucose homeostasis, but little research has linked NEOs exposure to gestational diabetes mellitus (GDM), which is the most common disease in pregnancy. We here aimed to investigate the association between NEOs exposure and GDM occurrence. Methods: 100 pregnant women who completed a 75 g oral glucose tolerance test (OGTT) at 24–28 weeks of gestation were enrolled. Urinary concentrations of seven widely used NEOs were quantified using ultra-high performance liquid chromatography multiple reaction monitoring mass spectrometry (UHPLC-MRM-MS/MS). Correlation analysis revealed the associations between NEOs concentrations and glucose homeostasis parameters. The toxic effects of thiamethoxam (TMX) and clothianidin (CLO) were assessed using pregnant mice, and the potential mechanism in impairing glucose disposition regarding brown adipose tissue (BAT) thermogenesis has been elucidated. Results: Among the 100 urine samples, 88 % were contaminated by NEOs with concentrations ranging from 2.50 to 491.34 nmol/L. TMX and CLO were the most frequently detected NEOs, highly detected in women with GDM. Moreover, we found statistically significant associations between TMX concentrations and 1hBG, and 2hBG. Exposure to mixed NEOs during gestation resulted in elevated glucose levels and impaired insulin sensitivity in normal pregnant and GDM mice models. In addition, we found the metabolic disorders induced by NEOs were linked to the deterioration of BAT thermogenesis in vivo. Conclusion: In general, we demonstrated that prenatal exposures to NEOs were associated with an increased risk of GDM by deteriorating the thermogenic capacity of BAT